Assessment of physiological responses and milk production in Jersey crossbred cows at different stratum of THI inside the cow barn - MANDAL, DILIP KUMAR; RAI, SAROJ; CHATTERJEE, A; BHAKAT, C; DUTTA, T K; GHOSH, M K (The Indian Journal of Animal Sciences, 2023)
Environmental heat stress is one of the restrictive factors for optimum production of dairy cows. Present study was conducted to assess alteration in cardinal physiological responses, heat tolerance indices and milk yield in Jersey crossbred cows at three levels of thermal humidity index (THI), viz. THI-1 (<72), THI-2 (72-80) and THI-3 (>80). THI levels significantly influenced rectal temperature (RT) and respiration rate (RR), but not the pulse rate. With increase in THI level 1 to 3, the RT and RR increased significantly by 0.75°F and 10.70 counts/min during morning and 0.92°F and 12.5 counts/min during afternoon, respectively. The respective enhancement between THI-2 to THI-3 was 0.48°F and 7.06/min in morning and 0.58°F and 7.45/min in afternoon. Among the cardinal physiological responses, breathing rate was the most diurnal variable parameter and it increased by 22-29% from 8:00 am to 2:00 pm with enhancement of stress levels fromTHI-1 to THI-3. Measures of heat tolerance indices revealed that cows were comfortable at THI-1 and discomfort levels were prominent at THI > 80. Low yielders (<10 kg/day) resisted natural heat stress by oriented decline in daily milk yield (DMY) and sustained DMY even at THI >80. In case of high yielders (>10 kg/day) increase in THI level 1 to 2, DMY did not drop significantly; in contrast, with increase of THI-2 to THI-3, the DMY declined. It was concluded that enhanced breathing rate was the most prominent bio-indicator of natural heat stress in Jersey crossbred cows and at THI>80 production decline due to natural heat stress was nonsignificant in low yielders, whereas highly significant in high yielders (more than 21%). It was recommended that at THI >80, inside of cow shed needs immediate amelioration measures to diminish production losses and high yielders (>10 kg/day) warrant more attention than low yielders during heat stress.